2015
DOI: 10.15698/mic2015.01.181
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct and competitive pathways confer the cellcidal actions of artemisinins

Abstract: The biological actions of artemisinin (ART), an antimalarial drug derived from Artemisia annua, remain poorly understood and controversial. Besides potent antimalarial activity, some of artemisinin derivatives (together with artemisinin, hereafter referred to as ARTs), in particular dihydroartemisinin (DHA), are also associated with anticancer and other antiparasitic activities. In this study, we used baker’s yeast Saccharomyces cerevisiae as cellular and genetic model to investigate the molecular and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…It has been shown that the respiratory growth (i.e., on non-fermentable media) of yeast is especially sensitive to artemisinins2324. On fermentable media, yeast is much less sensitive to artemisinins26. The former inhibition is attributed to a partial mitochondrial membrane depolarization and the latter a relatively general, and mostly heme-mediated toxicity26.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the respiratory growth (i.e., on non-fermentable media) of yeast is especially sensitive to artemisinins2324. On fermentable media, yeast is much less sensitive to artemisinins26. The former inhibition is attributed to a partial mitochondrial membrane depolarization and the latter a relatively general, and mostly heme-mediated toxicity26.…”
Section: Resultsmentioning
confidence: 99%
“…On fermentable media, yeast is much less sensitive to artemisinins26. The former inhibition is attributed to a partial mitochondrial membrane depolarization and the latter a relatively general, and mostly heme-mediated toxicity26. We asked what effects of the mitochondria-targeting will have on these activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not know yet what causes these differences but are actively working to unravel this mystery. Regarding the role of heme, we found when reacting with artemisinins, it appears to exert a general damaging effect on the cell, much less potent as well as less specific than the mitochondrial membrane depolarizing action of artemisinins [9]. These two different actions can be utilized to explain respectively the different properties of artemisinins against malarial parasites and cancer cells: one is very robust and selective, via membrane depolarization, whereas the other one, mediated by heme, is more general and much less potent.…”
mentioning
confidence: 84%